Digital Divide and A Spatial Investigation of Convergence in ICT Development Across Provinces in Indonesia - Herdina Dwi Ramadhanti; Erni Tri Astuti (Jurnal Aplikasi Statistika & Komputasi Statistik, 2020)
In the digital era, technology plays a much bigger role all over the world including in Indonesia. In fact, Indonesia’s ICT Development Index (IDI) has improved over time. However, it is noticeable that disparities among regions in regards to ICT development are still wide resulting in digital divide. This paper aims to examine the convergence of regions with regard to ICT development and analyze the key factors which drive the convergence process using annual data from 2015 to 2019. Spatial panel regression method is used to test for absolute and conditional beta convergence. The results reveal that there is evidence for the existence of absolute and conditional convergence in regards to ICT development in Indonesia. Regarding conditional convergence, the convergence process takes a shorter time to reach half-time convergence by taking into account several control variables consisting of output in ICT sector, FDI, and government allocation on education. In addition, the significant spatial correlation among provinces shows that the growth of neighboring provinces’ ICT development also contributes to the convergence process. This finding implies that the digital divide has declined and the factors mentioned above are important instruments to help bridge the digital divide.